الطريقة الرياضية لتحسين أداء عمل عناصر أجهزة الحماية الزاجلية - زاهد بدور (Tishreen University, 2019)
يعرض هذا البحث طريقة جديدة لتحسين أداء عمل أجهزة الحماية الزاجلية, وذلك من أجل إمكانية زيادة سرعة عمل الحمايات وزيادة موثوقية أداء الشبكات الكهربائية, وذلك باستخدام نماذج رياضية تم الاعتماد عليها لصياغة أداء عمل الحمايات للعناصر الكهربائية الأكثر انتشاراً في شبكات التوزيع ذات التوتر المتوسط. بينت النتائج إمكانية خفض درجة الانتقائية للحماية عن طريق حساب التابع  الذي يعبر عن فعالية البنى المختلفة لأجهزة الحماية وفقاً لمعيار الانتقائية الأمر الذي أدى إلى أفضلية زيادة دقة أداء عمل عناصر التأخير الزمني للحمايات حتى  أو حتى  بهدف خفض درجة الانتقائية إلى 0.2sec الأمر الذي يسمح بالحد من حجم الأعطال وزمن استعادة عناصر الشبكات في جميع أنواع القصر ( S.C). This research presents a new method for improving the performance of working of the elements of relay protection devices that so as to increase the speed of the protection operation and the reliability of electrical nets performance by using mathematical models, upon which to depend for making the performance of working of the most widespread electrical distribution nets of medium voltage. The results showed the possibility of reducing the selective degree of protection by computing the function which expresses the different structure efficiency of the protection devices due to the selective standard. This case leads to the preference of increasing the performance precision of the operation of the time delay elements for the protections till 00.25 sec or till 0.05 sec, aiming to decrease the selective degree to 0.2sec, which in turn was allowed to reduce the defects volumes and the time of net words elements recovery in all kinds of shortening circuit (s.c).